2018
DOI: 10.1080/21645515.2018.1430541
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SP1683 as a pneumococcal protein that is protective against nasopharyngeal colonization

Abstract: Serotype-independent protein-based pneumococcal vaccines represent attractive alternatives to capsular polysaccharide-based vaccines. The aim of this study was to identify novel immunogenic proteins from Streptococcus pneumoniae that may be used in protein-based pneumococcal vaccine. An immunoproteomics approach and a humanized severe combined immunodeficient mouse model were used to identify S. pneumoniae proteins that are immunogenic for the human immune system. Among the several proteins identified, SP1683 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Indeed, we found that the protective hit rate was highest in the pool of proteins that induced higher responses in all the screens. The 16 protective antigens that we identified have not been reported previously as conferring protection, with the single exception of SP1683, which was reported as a Th17-dependent antigen that protects against colonization while this article was being prepared (32). While the protection against colonization by any single antigen did not approach that of SPWCV in mouse models (Fig.…”
Section: Figmentioning
confidence: 77%
“…Indeed, we found that the protective hit rate was highest in the pool of proteins that induced higher responses in all the screens. The 16 protective antigens that we identified have not been reported previously as conferring protection, with the single exception of SP1683, which was reported as a Th17-dependent antigen that protects against colonization while this article was being prepared (32). While the protection against colonization by any single antigen did not approach that of SPWCV in mouse models (Fig.…”
Section: Figmentioning
confidence: 77%
“…8 No. 2 been analyzed in clinical trials and their protective effects are still limited to a subset of pneumococcal strains [12,13]. The candidate protein should mostly be well-conserved among pneumococcal serotypes and be able to stimulate T-helper cells, resulting in a strong memory response [13].…”
Section: Introductionmentioning
confidence: 99%